2011
DOI: 10.1016/j.annepidem.2011.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Are Current Law Enforcement Strategies Associated with a Lower Risk of Repeat Speeding Citations and Crash Involvement? A Longitudinal Study of Speeding Maryland Drivers

Abstract: PURPOSE To determine whether traffic court appearances and different court verdicts were associated with risk of subsequent speeding citations and crashes. METHODS A cohort of 29,754 Maryland drivers ticketed for speeding who either went to court or paid fines by mail in May/June 2003 was followed for 3 years. Drivers appearing in court were categorized by verdicts: 1) not guilty, 2) suspension of prosecution/no prosecution (STET/NP), 3) case dismissed, 4) probation before judgment and fines (PBJ), or 5) fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Due to the acute nature of automobile injuries, claims for automobile accident injuries were based on a single medical visit (hospitalization or medical visit). In cohort analyses of cancer followed by automobile accident injuries, individuals were excluded if they had prior automobile accident injuries because multiple accidents may indicate a common underlying cause . Otherwise, the analyses were based on the models for cancer and AD.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the acute nature of automobile injuries, claims for automobile accident injuries were based on a single medical visit (hospitalization or medical visit). In cohort analyses of cancer followed by automobile accident injuries, individuals were excluded if they had prior automobile accident injuries because multiple accidents may indicate a common underlying cause . Otherwise, the analyses were based on the models for cancer and AD.…”
Section: Methodsmentioning
confidence: 99%
“…To combat the problem of speed-related crashes, Cambodia may consider focusing road-safety efforts around motorcycle speed control. This might be accomplished through a combination of road smoothing/traffic calming (Grundy et al, 2009), increased enforcement (Li et al, 2011), and setting speeds that are appropriate for the roadway (Elvik, Vaa, Erke, & Sorensen, 2009) – all shown to be promising interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors found that drivers who paid fines and received points were no different from those who were declared not guilty in regard to the potential to receive a speeding citation in the future. The authors conclude that severe penalties including fines and points have a limited effectiveness in reducing speeding and crashes (Li et al, 2011). They add that, “reviews of studies addressing the effectiveness of countermeasures on traffic violations have concluded that receiving an occasional fine for speeding is merely an inconvenience rather than an effective deterrent for some drivers” (Li et al, 2011, p. 645).…”
Section: Traffic Tickets As Revenue or Public Safety Measuresmentioning
confidence: 99%